(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Preeclampsia is a major contributor to maternal and perinatal morbidity and mortality worldwide, particularly in developing countries. Early identification of women at risk remains challenging because of the multifactorial nature of the disease. The Gestosis scoring system, based on maternal clinical risk factors, offers a simple, practical, and cost-effective method for early prediction of hypertensive disorders of pregnancy. Materials and Methods: This prospective cohort study was conducted in a private tertiary care hospital over a period of six months, from July 2025 to December 2025. A total of 350 pregnant women beyond 36 weeks of gestation with gestational hypertension or newly detected hypertension were initially assessed for eligibility. After exclusion of 20 women due to incomplete records and failure to meet the study criteria, 330 women were included in the final analysis. Detailed clinical history, obstetric parameters, and relevant biochemical data were collected. Gestosis score was calculated for each participant, and all patients were followed up till delivery and during the postpartum period. Statistical analysis was performed to determine the association between gestosis score and the development of preeclampsia. Results: The proportion of severe preeclampsia was significantly higher among women with a gestosis score greater than 3 (42.7%) compared to those with a score of 3 or less (6.4%), with a relative risk of 6.7 (p<0.001). Significant associations were observed between preeclampsia and maternal risk factors such as elevated mean arterial pressure (>85 mmHg), anemia, and increased body mass index (p<0.01). Extremes of maternal age and primigravida status were also associated with a higher proportion of severe disease. A reduction in risk was observed among patients receiving low-dose aspirin; however, subgroup analysis was not performed. Conclusion: Gestosis scoring is an effective and practical risk stratification tool in hypertensive pregnancies for identifying higher-risk women within a hypertensive population at risk of developing preeclampsia. Incorporation of this scoring system into routine antenatal care may facilitate timely intervention, closer surveillance, and improved maternal and fetal outcomes.